2020
DOI: 10.3389/fimmu.2020.01811
|View full text |Cite
|
Sign up to set email alerts
|

Household Contacts of Leprosy Patients in Endemic Areas Display a Specific Innate Immunity Profile

Abstract: Leprosy is a chronic infectious disease, caused by Mycobacterium leprae, that can lead to severe lifelong disabilities. The transmission of M. leprae is continuously ongoing as witnessed by the stable new case detection rate. The majority of exposed individuals does, however, not develop leprosy and is protected from infection by innate immune mechanisms. In this study the relation between innate immune markers and M. leprae infection as well as the occurrence of leprosy was studied in household contacts (HCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
4
21
0
1
Order By: Relevance
“…Separate evaluation of biomarkers, however, indicated that ApoA1 differed significantly in these patients with PB leprosy from controls, corroborating the potential of ApoA1 as a biomarker for PB leprosy ( van Hooij et al., 2019 ). M. leprae -exposed HCs in South Korea showed a similar ApoA1 response as the patients with PB leprosy, as observed previously in Bangladesh ( van Hooij et al., 2020 ). In contrast to our findings in Bangladesh ( van Hooij et al., 2020 ), R values of S100A12 in contacts and patients with PB leprosy were similar to those of healthy controls in South Korea.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Separate evaluation of biomarkers, however, indicated that ApoA1 differed significantly in these patients with PB leprosy from controls, corroborating the potential of ApoA1 as a biomarker for PB leprosy ( van Hooij et al., 2019 ). M. leprae -exposed HCs in South Korea showed a similar ApoA1 response as the patients with PB leprosy, as observed previously in Bangladesh ( van Hooij et al., 2020 ). In contrast to our findings in Bangladesh ( van Hooij et al., 2020 ), R values of S100A12 in contacts and patients with PB leprosy were similar to those of healthy controls in South Korea.…”
Section: Discussionsupporting
confidence: 85%
“…M. leprae -exposed HCs in South Korea showed a similar ApoA1 response as the patients with PB leprosy, as observed previously in Bangladesh ( van Hooij et al., 2020 ). In contrast to our findings in Bangladesh ( van Hooij et al., 2020 ), R values of S100A12 in contacts and patients with PB leprosy were similar to those of healthy controls in South Korea. Leprosy is no longer endemic in this country; it has to be taken into account that the frequency of exposure to M. leprae , as well as other environmental pathogens, can definitely influence biomarker levels, stressing the importance of quantitative measurements.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings were corroborated in additional studies, also studying these CCGF in cohorts in China, Brazil, and Ethiopia with a different genetic background. 19,49 However, most PB leprosy patients and household contacts responded similarly to the M leprae antigens. Further research on the mechanisms that determine progression of M leprae infection to disease may allow the identification of biomarkers differentiating PB from healthy exposed individuals.…”
Section: Circul Atory B Iomarker S: B E Yond the Antibody Re S P On S Ementioning
confidence: 98%
“…Exposure to M leprae also affects the innate immune response of contacts of lepromatous patients; levels of ApoA1 and S100A12 similar to those of PB patients have been observed in contacts of leprosy patients. 49 We hypothesize that in these individuals there is a constant battle between the host and the bacterium:…”
Section: From Infec Ti On To D Is E a S E: Hous Ehold Contac Ts In Vivo D Is E A S E Model?mentioning
confidence: 99%